Nuclear energy: an option for the present and for the future - González Jiménez, Antonio (Razón y fe, 2018)
The increasing consumption of energy and the competition at the economic level of the (recent) emerging countries, has made energy a global problem. Faced with a growing consumption of traditional energies, fossil fuels -that is to say: coal, oil and natural gas- nuclear energy appears as an invaluable help due to its reliability, safety and low cost. In this article, in addition to reviewing our past and present energy, we bet -not naively- on the need to maintain and sustain nuclear energy among us.